When the Hidden Issue of Elder Abuse Leads to Death: Do Not Neglect Elder Neglect. (March 2022) - Mazzotti, Maria Carla; Fais, Paolo; Amadasi, Alberto; Pelletti, Guido; Giovannini, Elena; Giorgetti, Arianna; Pelotti, Susi
Abstract : Abstract: It is well known that elder neglect entails a number of physical and psychological consequences, as well as being an independent risk factor for death. In the present study, we describe 5 forensic cases of death of older adults where the diagnosis of neglect only emerged postmortem through the combination of the scene investigation, the often-scarce circumstantial data, and the autopsy findings. The gathering of this information allowed the presence of risk factors—not previously assessed or reported—to be identified. Nevertheless, complete medical information was lacking both for the isolation of the victims with their caregivers and for the absence of every social and health support in self-neglect. More research is needed also in the forensic pathology field with standardized methods to contribute to prevention strategies and to avoid that victims of elder neglect remain hidden also after death.